Evaluasi Kesuksesan Implementasi SLA Pada Mobile PLIK Bangka Belitung - Harrizki Arie Pradana; Ellya Helmud; Parlia Romadiana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Information technology that is currently developing does not only apply to the world of information technology but has developed into other fields of work that require information technology to support the needs of their field. Services in information technology have been implemented by the District Internet Service Center (PLIK) Bangka Belitung to support government programs. Research conducted at PLIK aims to see and assess how PLIK's performance, especially Mobile PLIK, to the service level of their partners' satisfaction. During the PLIK research, researchers wanted to measure their level of service. The level of service that is measured is by looking at the implementation of the SLA (Service Level Agreement) that they have contracted with the user to what extent. So, the researchers took the data by observation, interviews, and questionnaires. After all, data is needed, the COBIT 4.0 Framework becomes a reference for researchers to examine this service level with the Delivery and Support (DS) domain on each item. The conclusion from the whole research process is that Mobile PLIK has measured their service maturity level (Maturity Level) at layer 4, namely Managed and Measurable. However, there are several districts that are still at layer 3, namely Define. Define that they have targeted and planned every measure of their work steps and of course they can improve the services provided to partners and be reciprocal to partner satisfaction with PLIK. Unlike the case with Define, layer 4 is Managed and Measurable, which means that Mobile PLIK has been organized and can be measured in conducting every agreement between partners and PLIK, so that its implementation can be accounted for every item in the domain.